A remote islanding detection and control strategy for photovoltaic-based distributed generation systems. (15th May 2015) - Bayrak, Gökay
Graphical abstract: Highlights: This study presents a new remote islanding detection method for PV based DG systems. An uncomplicated VLSI based structure for voltage drifting detection is proposed with FPGA. The proposed method was verified by the developed PV testbed constituted in the laboratory. The islanding detection time is 1.65 ms even in a resonant condition. The proposed method is independent from inverter & load so it can be easily implemented. Abstract: This study presents a new remote islanding detection method and control system for photovoltaic (PV) based Distributed Generation (DG) systems. The proposed method monitors and controls the grid, local load and the output of the PV inverter in real time with the communication of circuit breakers. The proposed remote control system detects the changes in the currents of the circuit breakers, frequency, and the voltages by checking the defined threshold values at all electrical branches of the PV system. The proposed islanding detection algorithm was implemented by a low-cost FPGA board. The control system was also designed by considering a Very Large Scale Integration (VLSI) structure. The proposed method was verified by a developed prototype PV system constituted in the laboratory. The proposed control system was checked in a resonance condition with an active power match, and the verified results indicated that the developed system was also independent of the load and the inverter. Islanding detection time is approximately 1.65 ms even in a worst-case operational scenario, and this is a significantly shorter response time according to the existing standards. The proposed method presents a realistic solution to islanding, is easy to implement, and is suitable for real system applications. The method also provides a reliable islanding detection and presents a low-cost solution to the subject.